Migration of Rod into Retroperitoneal Region: A Case Report and Review of the Literature - BAYRİ, YAŞAR (My University, 2014)
Spinal stabilization with fusion is the widely used method for traumatic or pathologic fracture of spine, spinal stenosis, and spondylolisthesis. Complications may emerge during or after the operations. Infection, hematoma and neurological deficits are early noticed findings. Screw and/or rod fractures present in long-term after surgery. Rod migration in out of the spinal column is a rare entity. A 67-year-old woman was visited our clinic for right leg pain. She had a previous spinal instrumentation surgery for spondylolisthesis in another center 6 years before. After radiological work-up, a distally migrated rod piece was observed in the retroperitoneal portion. The patient was operated for degenerative change; old instruments were replaced and extended to the L2 level with posterior spinal fusion. After the operation, her right leg pain improved. The asymptomatic migrated rod piece has regularly been followed clinically and radiologically, since then. Although it has rarely been reported, migration of the instrumentation material should be kept in mind. Spinal fixation without fusion makes the mechanical system vulnerable to motion effects of spine, especially in a degenerative and osteoporotic background. Long-term, even life-long follow-up is necessary for late term complications.
Keywords: Spondylolisthesis; Lumbar spine; Migration; Spinal instrumentation